Effect of cage distance on fly density in the village of Sukoharjo - santosoa, bachtiar (Journal of Global Research in Public Health, 2020)
The high number of fly density in a place can cause health problems in the settlements around the place. Tukdadap Hamlet, Sukoharjo Village, Wilangan Nganjuk District. Almost all villagers have animal sheds, it is not uncommon for the cage to become one with the house, the cleanliness of the cage is not paid attention to resulting in the accumulation of animal waste, the distance between the cage and the house is less than 10 meters. This study aims to determine the relationship between the distance of the cage and the house on the density of flies in Sukoharjo Village. This research method is analytic observational with cross sectional approach. The sample in this study were residents of Tukdadap Hamlet, Sukoharjo Village, which had animal sheds, totaling 43 respondents. The statistical test used is linear regression. The statistical test results obtained p-value of 0.634 (> 0, 05) which indicates that there is no relationship between the distance of the cage and the house on the density of flies. It is advisable for residents of Tukdadap hamlet to always keep the environment clean, clean the stables, and place the cattle sheds far from the house to prevent the emergence of fly vectors that cause diarrhea.